The Impact of Sexual Assault Nurse Examiner Programs on Criminal Justice Case Outcomes: A Multisite Replication Study. (May 2014) - Campbell, Rebecca; Bybee, Deborah; Townsend, Stephanie M.; Shaw, Jessica; Karim, Nidal; Markowitz, Jenifer
To address the underreporting and underprosecution of adult sexual assaults, communities throughout the United States have implemented multidisciplinary interventions to improve postassault care for victims and the criminal justice system response. One such model is the Sexual Assault Nurse Examiner (SANE) Program, whereby specially trained nurses provide comprehensive psychological, medical, and forensic services for sexual assault. In this study, we conducted a multisite evaluation of six SANE programs (two rural programs, two serving midsized communities, two urban) to assess how implementation of SANE programs affects adult sexual assault prosecution rates. At each site, most sexual assaults reported to law enforcement were never referred by police to prosecutors or were not charged by the prosecutor's office (80%-89%). Individually, none of the sites had a statistically significant increase in prosecution rates pre-SANE to post-SANE. However, when the data were aggregated across sites, thereby increasing statistical power, there was a significant effect such that cases were more likely to be prosecuted post-SANE as compared with pre-SANE. These findings suggest that the SANE intervention model does have a positive impact on sexual assault case progression in the criminal justice system. Nevertheless, there is still a pressing need for improvement as the vast majority of both pre-SANE and post-SANE resulted in nonreferral/no charges filed.